Production and characterization of pyrolysis oil using waste polyethylene in a semi batch reactor - Gaurh P.; Pramanik H. (My University, 2025)
Plastic waste, polyethylene has been used as a feed stock for the production of valuable hydrocarbons via thermal pyrolysis. The thermal pyrolysis of waste polyethylene has been investigated in a specially designed semi batch reactor with L/D ratio of 1.2. Polyethylene sample of 50 g is used as feed using different reaction temperatures from 500-800°C. The reaction time of 30 min is maintained irrespective of variation in other experimental conditions. The pyrolysis oil are characterized using API gravity, flash and fire point, calorific value, carbon residue, proximate analysis, ASTM distillation and GC-FID, The maximum liquid yield of 72.6% is obtained at a temperature of 800°C, whereas the liquid yield was 61.5% at the temperature of 500°C. Though the liquid yield is maximum at 800°C, the pyrolysis oil solidifies at 32°C, which indicates higher paraffins are more. The solid char produced was minimum (9.4 wt %) at 800°C and it was maximum (20.44 wt. %) at 500°C. There is minor change in gaseous hydrocarbon yield irrespective of pyrolysis temperature. The liquid yield obtained at 700°C exhibit the properties similar to commercial diesel with boiling point range 270-320°C i.e., similar to beyond 50% distillate recovery as tested in ASTM D86. GC-FID tests of pyrolysis oil (700°C) gives comparable GC characteristics of commercial diesel. © 2018, National Institute of Science Communication and Information Resources (NISCAIR). All rights reserved.